Development of nanobody-based flow-through dot ELISA and lateral-flow immunoassay for rapid detection of 3-phenoxybenzoic acid. Issue 14 (24th March 2021) - Zhang, Can; Wu, Xiaoxiao; Li, Dongyang; Hu, Jinnuo; Wan, Debin; Zhang, Zhen; Hammock, Bruce D.
Abstract : Flow-through dot ELISA and gold nanoparticle lateral-flow immunoassay based on nanobodies were developed for detecting 3-PBA. The sensitivity of nanobody-based flow-through dot ELISA is 10-fold higher than that of gold nanoparticle lateral-flow immunoassay. Abstract : As a major metabolite of pyrethroid pesticides, 3-phenoxybenzoic acid (3-PBA) can be an indicator of health risk and human exposure assessment. Based on nanobodies (Nbs), we have developed a rapid flow-through dot enzyme linked immunosorbent assay (dot ELISA) and gold nanoparticle (GNP) lateral-flow immunoassay for detecting 3-PBA. The limit of detection (LOD) values for detecting 3-PBA by flow-through dot ELISA and GNP lateral-flow immunoassay were 0.01 ng mL −1 and 0.1 ng mL −1, respectively. The samples (urine and lake water) with and without 3-PBA were detected by both nanobody-based flow-through dot ELISA and GNP lateral-flow immunoassay, as well as liquid chromatography-mass spectrometry (LC-MS) for validation. There was good consistency between the results of the immunoassays. This demonstrated that the two developed nanobody-based immunoassays are suitable for rapid detection of 3-PBA.